Recognition Versus Action: An Examination of Physical Education, Physical Activity, and Youth Sport Policy in Ireland (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Policy in physical education (PE), physical activity (PA), and youth sport (YS) plays a pivotal role in shaping youth health and wellbeing. A critical distinction exists between policies that acknowledge these domains by recognising their importance and those that address them through defined actions, strategies, and interventions. The aim of this study was to examine how national policies in Ireland conceptualise and engage with PE, PA, and YS, and to evaluate the extent to which policies move from acknowledgement to implementation across these domains.Methods: A content mapping analysis of national policy documentation related to PE, PA, and YS in Ireland was conducted. A three-step systematic approach of policymaker identification, policy identification, and domain alignment was followed. Deductive content analysis determined domain alignment of active policy. An inductive matrix was constructed to classify whether each domain was acknowledged (i.e. recognised or referenced without concrete plans) or addressed (i.e. accompanied by specific actions, implementation strategies, or targets), adapted from Chhetri & Zacarias (2021). The lead author independently coded the data, resolving discrepancies through discussion with co-authors to ensure consistency and rigour.Results: Findings reveal fragmented engagement across the three domains. PA was most frequently addressed, with 55.6% (n = 10) of policymakers including concrete strategies. In contrast, 22.2% (n = 4) addressed YS, and only one addressed both PA and PE. A single policymaker addressed all three domains explicitly. Notably, PE was never addressed in isolation and was often embedded under broader education or health frameworks. While 33.3% (n = 6) acknowledged all three domains, 38.9% (n = 7) acknowledged only PA, often without specifying implementation measures.Conclusion: These findings highlight the need for a more coherent and balanced policy landscape in PE, PA, and YS. Moving from acknowledgement to implementation is essential to realising intended health outcomes. Greater integration and specificity in policy design can support more equitable representation of domains, youth health, and foster holistic, lifelong engagement with physical activity among youth.